2015
DOI: 10.1159/000376552
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Profile and New IASLC/ATS/ERS Classification Provide Additional Prognostic Information about Lung Adenocarcinoma: A Study of 125 Patients from Brazil

Abstract: Aim: To show additional prognostic information about the mutational profile and new International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society (IASLC/ATS/ERS) classification of adenocarcinoma (ADC) in patients without epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor treatments. Methods: In human lung ADC patients (n = 125), including 24 lepidic, 67 acinar, 23 papillary, and 11 solid predominant subtypes, EGFR and KRAS were sequenced, and anapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
5
11
1
4
Order By: Relevance
“…This supports the genetic heterogeneity of NSCLC among geographic regions and also underscores the need for extending the study to other countries of South and Central America. Several studies conducted in Brazil reported 24% of EGFR mutation in adenocarcinomas [30], in agreement with De Melo et al, who reported 21.6% [37]. Interestingly, in this study most are rare mutations, while common mutations in exon 19 and 21 represent only 40% of the total mutations.…”
Section: Discussionsupporting
confidence: 91%
“…This supports the genetic heterogeneity of NSCLC among geographic regions and also underscores the need for extending the study to other countries of South and Central America. Several studies conducted in Brazil reported 24% of EGFR mutation in adenocarcinomas [30], in agreement with De Melo et al, who reported 21.6% [37]. Interestingly, in this study most are rare mutations, while common mutations in exon 19 and 21 represent only 40% of the total mutations.…”
Section: Discussionsupporting
confidence: 91%
“…The mean size of the tumors was 2.8 AE 2.1 cm (range; 0. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Non‐small cell lung carcinoma (NSCLC) accounts for 85% of all lung cancer where adenocarcinoma (AC) is the most common histology . The strongest prognostic factors of survival for patients with NSCLC are the TNM stage , advanced age, history of weight loss , ethnicity , and some genetic mutations (i.e., EGFR, K‐RAS, p53) .The three major NSCLC histological types; squamous cell carcinoma (SCC), AC, and large cell carcinoma (LCC) have also been shown to influence survival in some studies , but not in all . Bronchioloalveolar adenocarcinoma (BAC) that was described as a subtype of AC, has been thought to have a better prognosis than non‐BAC adenocarcinomas .…”
mentioning
confidence: 99%
“…Entre os pacientes testados, 35,3% eram positivos para EGFR, dado similar ao percentual relatado em Bacchi et al, que identificaram 30,4% de EGFR positivo entre todas as amostras testadas (Bacchi et al, 2012). Por outro lado, a maioria dos estudos publicados sobre o status de mutação do EGFR reporta um percentual menor de pacientes positivos no Brasil, América Latina, Austrália, Estados Unidos e Europa (de Castro et al, 2017;Pan et al, 2013;de Marinis et al, 2014;Gridelli et al, 2014;Honma et al, 2014;Carneiro et al, 2014;de Melo et al, 2015;Arrieta et al, 2015), exceto Coreia do Sul e Taiwan (de Castro et al, 2017). Em relação à mutação do KRAS, a taxa de pacientes positivos é maior em comparação com a literatura (Bacchi et al, 2012;Carneiro et al, 2014;de Melo et al, 2015;Arrieta et al, 2015), provavelmente devido ao número reduzido de pacientes testados neste estudo (n = 9 Melo et al, 2015), mas menor que na Coreia do Sul e em Taiwan (de Castro et al, 2017).…”
Section: Discussionunclassified
“…Por outro lado, a maioria dos estudos publicados sobre o status de mutação do EGFR reporta um percentual menor de pacientes positivos no Brasil, América Latina, Austrália, Estados Unidos e Europa (de Castro et al, 2017;Pan et al, 2013;de Marinis et al, 2014;Gridelli et al, 2014;Honma et al, 2014;Carneiro et al, 2014;de Melo et al, 2015;Arrieta et al, 2015), exceto Coreia do Sul e Taiwan (de Castro et al, 2017). Em relação à mutação do KRAS, a taxa de pacientes positivos é maior em comparação com a literatura (Bacchi et al, 2012;Carneiro et al, 2014;de Melo et al, 2015;Arrieta et al, 2015), provavelmente devido ao número reduzido de pacientes testados neste estudo (n = 9 Melo et al, 2015), mas menor que na Coreia do Sul e em Taiwan (de Castro et al, 2017). Os regimes baseados em platina foram a prática clínica mais comum como terapia de primeira linha (83,6%), conforme recomendado pelas diretrizes nacionais e internacionais (NCCN, 2017;de Sa et al, 2016) e também foram o tratamento predominante nos estudos de dados do mundo real publicados na Ásia-Pacífico, América do Norte e Europa (de Castro et al, 2017;Davis et al, 2015;Sacher et al, 2015;Solem et al, 2015a;Davies et al, 2017).…”
Section: Discussionunclassified